PENGARUH BRAND IMAGE DAN BRAND LOVE TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER ENGAGEMENT SEBAGAI MEDIASI (Studi Pada Konsumen Produk APPLE di Universitas Muhammadiyah Surakarta) - Muhammad Irly Artha Vikranof; Irmawati (POLITEKNIK LP3I JAKARTA, 2024)
Indonesia is a developing country with the largest population, making it a potential market with high growth, one of which is the APPLE Company. APPLE Company This study aims to determine the effect of customer loyalty on consumers of APPLE products in the campus area of Universitas Muhammadiyah Surakarta. This research method uses a quantitative approach. The population in this study were students of Universitas Muhammadiyah Surakarta who used Apple products. The sampling used in this research is purposive sampling where this technique is used to determine the research sample with consideration of certain criteria. Through Maholtra's calculations, the minimum sample required is 112 respondents who use Apple products, both male and female. In this study, the data source used is primary data source. The data collection method used in this study was the distribution of questionnaires. The data analysis technique used in this research is Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study are Brand Image has a positive and significant effect on Customer Engagement. Brand Image has a positive and significant effect on Customer Loyalty. Brand Love has a positive and significant effect on Customer Engagement. Brand Love has a positive and significant effect on Customer Loyalty. Brand Image has a positive and significant effect on Customer Loyalty which is mediated by Customer Engagement. Brand love has no effect on Customer loyalty mediated by Customer Engagement.